Experimental studies of profile joints of machine parts under cyclic loading conditions - V. A. Ilyinykh (Омский научный вестник)
The increasing demands on the quality of machines, in particular multipurpose CNC machines, determine the tasks aimed at improving the designs of their critical components. The aim of the work is to ensure the accuracy, contact rigidity and durability of torquetransmitting connections of spindle assemblies during reusable replacements of auxiliary tools based on the use of conical profile connections with an equiaxed contour. The paper presents the results of experimental studies of these compounds on models that are made of optically active materials, which allows us to visually study the processes of contact interaction of profile parts under cyclic loading conditions. The method of static photoelasticity in the study of flat profile joints with an equiaxed contour made it possible to establish based on the analysis of isochrome patterns, that the change in the values of maximum tangential stresses per revolution of the profile joint is subject to a pulsation cycle.